Adversity Quotient of Jujitsu Athletes Who Have Experienced Minor Post-Competition Injuries: Adversity Quotient Atlet Jujitsu yang Pernah Mengalami Cedera Ringan Pasca Pertandingan - Lindha, Maretha; Nastiti, Dwi (Indonesian Journal of Innovation Studies, 2023)
This research is motivated by the lack of Adversity Quotient in jujitsu athletes who have experienced minor post-match injuries where there are still many jujitsu athletes at Kemala Bhayangkari 3 Porong High School, Muhammadiyah University of Sidoarjo and Wijaya Putra University who lack the fighting power to achieve the achievements they want due to the injuries they suffered. Adversity quotient is a very important thing for an athlete to have. Adversity quotient can be influenced by several aspects, one of which is control (self-control). This type of research is a descriptive quantitative research method, this method is the right method to find out the results of this study which aims to determine the effect of the adversity quotient of athletes who have experienced minor post-match injuries. The total population in this study were 60 athletes. The sampling technique used is the Purposive Sampling Technique. Collecting data using a psychological scale with a Likert scale model. Data analysis in this study used descriptive statistical analysis assisted by the SPSS 16.0 for windows program. The results of this study indicate that the adversity quotient of male and female jujitsu athletes has different levels, male athletes have a more dominant level and in terms of aspects, aspects of control (self control) are more dominant.